New Developments on Ostrowski Type Inequalities via q-Fractional Integrals Involving s-Convex Functions - Xiaoming Wang; Khuram Ali Khan; Allah Ditta; Ammara Nosheen; Khalid Mahmood Awan; Rostin Matendo Mabela (Journal of Function Spaces)
In the present paper, q-fractional integral operators are used to construct quantum analogue of Ostrowski type inequalities for the class of s-convex functions. The limiting cases include the nonfractional existing cases from literature. Specially, Ostrowski type inequalities for q-integrals and Ostrowski type inequalities for convex functions are deduced.